Alterations in leaf photosynthetic electron transport in Welsh onion (Allium fistulosum L.) under different light intensity and soil water conditions. (29th September 2020) - Liu, X.; Gao, S.; Liu, Y.; Cao, B.; Chen, Z.; Xu, K.
Abstract: Welsh onions ( Allium fistulosum L.) are often affected by stressful environments, such as high light and drought, during summer cultivation, which hinders their growth. We used CO2 assimilation, OJIP transient and MR curves to analyse the photosynthetic characteristics of Welsh onion. The results showed that single high light stress caused a decrease in the net photosynthesis rate through stomatal limitation, while the single drought treatment and the combined stress induced nonstomatal limitation. FO and FJ increased, Fm decreased, and a distinct K‐phase was induced. High light and drought stress blocked MR transients, leading to a gradual decrease in VPSI and VPSII‐PSI . In general, photosynthesis of Welsh onion was inhibited by high light and drought, which destroyed the receptor and donor side of PSII and reduced electron transport capacity of PSII and PSI. Abstract : The photosynthesis of Welsh onion was inhibited by high light and drought, which destroyed the receptor and donor side of PSII and reduced the electron transport capacity of PSII and PSI.